Adolescent Social Isolation Increases Cocaine Seeking in Male and Female Mice. - Fosnocht, Anne Q. (Behav Brain Res, 2018)
Childhood and adolescent adversity are associated with a wide range of psychiatric disorders, including an increased risk for substance abuse. Despite this, the mechanisms underlying the ability of chronic stress during adolescence to alter reward signaling remains largely unexplored. Understanding how adolescent stress increases addiction-like phenotypes could inform the development of targeted interventions both before and after drug use. The current study examined how prolonged isolation stress, beginning during adolescence, affected behavioral and neuronal underpinnings to the response to cocaine in male and female mice. Adolescent-onset social isolation did not alter the ability of mice to learn an operant response for food, nor influence food self-administration or motivation for food on a progressive ratio schedule. However, male and female social isolation mice exhibited an increase in motivation for cocaine and cocaine seeking during a cue-induced reinstatement session. Additionally, we demonstrated that adolescent-onset social isolation increased cocaine-induced neuronal activation, as assessed by c-Fos expression, within the nucleus accumbens core and shell, ventral pallidum, dorsal bed nucleus of the stria terminalis, lateral septum and basolateral amygdala. Taken together, the present studies demonstrate that social isolation stress during adolescence augments the behavioral responses to cocaine during adulthood and alters the responsiveness of reward-related brain circuitry.